MODIFIKASI MODEL POWER SOCCER WHEELCHAIR (KURSI RODA ELEKTRONIK POWER SOCCER) SEBAGAI ALAT LATIHAN OLAHRAGA POWER SOCCER BAGI ATLET TUNA DAKSA - Khuluq, Muhamad Husnul; Kurniawan, Arbi; Sunaryo, Fatoni Yanuar Ahmad Budi; Prayitno, Joko Adi (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
The purpose of this research is to create an electronic wheelchair sport designed for power soccer. The authors try modify Wheelchair Power Soccer (Electronic Power Wheel Chair Soccer) as a Tool of Power Soccer Sports Exercise for disable Athletes. The system is a solution and that the author gave innovation and contribute to the problem using the physically disabled football is still manual. We innovate to create electronic wheelchair as a tool for physically disable soccer athletes.Performance results wheelchair soccer power tools (electronic power wheelchair soccer) is driven in accordance with the commands sent by a joystick control that will be received by the control circuit ATmega8535 microcontroller and the output is the motion that moved by motor stepper. The tool is able to browse for a maximum of 32 minutes on flat roads with power supply of 6V 4.5 Ah. Optimal video radius of less than 5 meters.